Ventilated double glass window with reflective film: Modeling and assessment of performance. (June 2019) - Lago, Taynara G.S.; Ismail, Kamal A.R.; Lino, Fátima A.M.
Highlights: A robust numerical validated code is constructed based on the conservation equations. Optimum spacing between glass sheets reduce the heat gain is about 2.5 cm. Solar reflective film reduces solar energy gain in ventilated windows by about 63.4%. Glass thickness reduces the solar heat gain but optimum value must be used. Abstract: In the present study, the thermal behavior of a ventilated double glass window with a solar reflective film is numerically investigated and validated against results available in the literature. The objectives of the study are to develop a validated robust thermal model for the ventilated double glass window, make it versatile so that it can incorporate different inserts (such as reflective and absorptive films, etc.), different glass sheets and different fluids and can be integrated with other available design tools. The proposed ventilated double window is composed of two glass sheets separated by a gap forming a channel having a solar reflective film on the internal surface of outer glass sheet. The model is based on the equations of mass, momentum and the energy conservation equations in steady state. Boussinesq approximation is used to evaluate buoyancy term. The discretization of conservative equations is done using the finite volume method. A numerical code is developed and validated against available experimental and numerical results. Thermal performance of the ventilated double glass window is assessed under different conditions and the results show that in order to reduce the heat gain in the internal ambient, the optimum spacing between the glass sheets should be at least 2.5 cm. The solar reflective film in a ventilated double glass window can reduce the penetrating solar energy by about 64.7% in comparison with a traditional double glass window.